Ameliorating Effect of Aqueous Ginger Extract And Exercise On Insulin Resistance in Fructose Induced Type 2 Diabetic Rats Through Upregulation of Serum Sirtuin-1 - Seher Naeem; Muniza Saeed; Jawaria Ilyas; Asma Ashraf; Madiha Akram; Ruqayyah Nazir (Proceedings, 2023)
Introduction:The mounting prevalence of type 2 diabetes mellitus (T2DM) in developing countries calls for an immediate need to find novel treatment strategies that not only target its underlying pathological process but are also safe and cost effective.